Living beyond your feelings : controlling emotions so they don't control you - Meyer, Joyce, 1943- (FaithWords, 2011)
The average person has 70,000 thoughts every day, and many of those thoughts trigger a corresponding emotion. No wonder so many of us often feel like we are controlled by our emotions. Our lives would be much improved if we controlled them. In this book, the author examines the gamut of feelings that human beings experience. She discusses the way the brain processes and stores memories and thoughts, and then, emotion by emotion, she explains how we can manage our reactions to those feelings. In doing so she gives the reader a toolbox for managing the way we react to the onslaught of feelings that can wreak havoc in our lives. She blends the wisdom of the Bible with the latest psychological research. This is a comprehensive guide to the range of emotions that we feel every day and it shows us how to manage them, instead of letting them manage us. -- From publisher and book cover.